2005
DOI: 10.1002/bit.20577
|View full text |Cite
|
Sign up to set email alerts
|

Platelet cryopreservation using a trehalose and phosphate formulation

Abstract: Long-term storage of platelets is infeasible due to platelet activation at low temperatures. In an effort to address this problem, we evaluated the effectiveness of a formulation combining trehalose and phosphate in protecting platelet structure and function following cryopreservation. An annexin V binding assay was used to quantify the efficacy of the trehalose and phosphate formulation in suppressing platelet activation during cryopreservation. Of the platelets cryopreserved with the trehalose plus phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…This was not only confirmed by the trypan blue test: the same results were achieved by measurement of plating efficiency and total protein and in a cell proliferation assay 26. In the few available publications, the viability of the other types of cells was also enhanced after thawing, if trehalose was used as cryoprotective additive 13, 27, 28. In cryopreservation experiments, the function of the cells is often assayed only during the short culture period of a few days or even just in suspension directly after thawing 4, 11, 26.…”
Section: Discussionmentioning
confidence: 99%
“…This was not only confirmed by the trypan blue test: the same results were achieved by measurement of plating efficiency and total protein and in a cell proliferation assay 26. In the few available publications, the viability of the other types of cells was also enhanced after thawing, if trehalose was used as cryoprotective additive 13, 27, 28. In cryopreservation experiments, the function of the cells is often assayed only during the short culture period of a few days or even just in suspension directly after thawing 4, 11, 26.…”
Section: Discussionmentioning
confidence: 99%
“…of liposomes 64 and platelets. 65 In all of these applications, the ionic species are thought to increase the strength of the interactions present within the glassy matrix, through enhanced hydrogen bonding network, and demonstrated increased T g . In another application, the addition of glucose at 1:10 weight ratio improved the storage stability of glucose-6-phosphate dehydrogenase 66 ; glucose incorporation was thought to lower the free volume by filling in the void in the trehalose-protein glass, thus reducing molecular mobility, and consequently, improved stability.…”
Section: Unique Properties Of Trehalosementioning
confidence: 99%
“…Time and temperature of storage may influence bacterial growth, extent of phagocytosis, and the occurrence of complement-mediated killing. 128 Investigators have also found that the proliferation of Y. enterocolitica in RBCs may be decreased by storage at 0°C. [124][125][126] Lowering Component Storage Temperature Platelet storage at room temperature maintains platelet hemostatic efficacy, but this temperature provides a hospitable culture medium for many bacteria.…”
Section: Temperature and Time Of Storage Before Component Preparationmentioning
confidence: 99%